Keloid yang diterapi dengan kombinasi bedah listrik dan bedah beku pada seorang perempuan: sebuah laporan kasus dan tinjauan pustaka - NI Putu Ayu Riska Yunita Sari; Ketut Kwartantaya Winaya; Roslina Horo; Luh Nyoman Arya Wisma Ariani (Intisari Sains Medis, 2022)
Background: Keloids are nodular tumors with a soft and spongy consistency and have a shiny and soft surface. Lesions are absent in hair follicles and adnexal glands. The main mediators include transforming growth factor-beta (TGF-β), interleukin-1 (IL-1), interleukin-6 (IL-6), tumor necrosis factor (TNF), and vascular growth factor (VEGF). This case discusses the combination therapy of electrosurgery and frozen surgery in treating keloids. Case description: A woman, 34 years old, Indonesian, has complained of a lump on her left shoulder since ten years ago, which has been getting harder and harder, sometimes accompanied by pain and itching. There was a solitary hyperpigmented nodule in the left deltoid region with firm boundaries, geographic shape, measuring 5.7 cm x 4 cm x 0.8 cm, regular edges, and a smooth and shiny surface. On palpation, the consistency is firm and firm. Dermoscopy showed multiple erythema nodules with vascular structures in the form of arborizing vessels and linear irregular vessels. Electrocauter surgery was performed with cut mode and continued with cryo surgery and the antibiotic ointment gentamicin 0.1% topically every 12 hours on lesions that have undergone electrosurgery, frozen surgery, and paracetamol tablets 500 mg every 8 hours intraorally if pain. On the 36th day of observation, clinical improvement of the lesions was found. Conclusion: Cryo surgery is minimally invasive and can be combined with electrocautery surgery to reduce bleeding. The lesion improvement was seen after the combination treatment was given, although there were still hypertrophic scar lesions.   Latar belakang: Keloid merupakan tumor nodular dengan konsistensi lunak dan kenyal, memiliki permukaan berkilauan dan lunak. Lesi tidak terdapat pada folikel rambut dan kelenjar adneksal. Mediator utama meliputi transforming growth factor beta (TGF-β), interleukin-1 (IL-1), interleukin-6 (IL-6), tumor necrosis factor (TNF), dan vascular growth factor (VEGF). Kasus ini membahas terapi kombinasi bedah listrik dan bedah beku pada penanganan keloid. Kasus: Wanita, 34 tahun, warga negara Indonesia, mengeluh adanya benjolan pada bahu kiri sejak 10 tahun yang lalu yang semakin lama semakin keras, terkadang disertai rasa nyeri dan gatal. Pada regio deltoid sinistra didapatkan adanya nodul hiperpigmentasi soliter batas tegas, bentuk geografika, berukuran 5,7 cm x 4 cm x 0,8 cm, tepi reguler, permukaan halus dan mengkilat. Pada palpasi didapatkan konsistensi padat kenyal dan terfiksir. Dermoskopi didapatkan gambaran nodul eritema multipel dengan struktur vaskular berupa arborizing vessels dan linear irregular vessels. Dilakukan tindakan bedah listrik dengan mode cut dan dilanjutkan dengan bedah beku serta salep antibiotik gentamisin 0,1% tiap 12 jam secara topikal pada lesi yang telah dilakukan bedah listrik dan bedah beku dan parasetamol tablet 500 mg tiap 8 jam intraoral bila nyeri. Pengamatan hari ke 36 didapatkan perbaikan klinis lesi. Simpulan: Bedah beku merupakan tindakan invasif minimal dan dapat dikombinasikan dengan bedah listrik untuk mengurangi perdarahan selama tidakan dilakukan. Perbaikan lesi telihat setelah diberikan tindakan kombinasi walaupun masih terdapat lesi skar hiperterofik.